Sports Massage Can Welfare and Has Economic Benefits for PJKR FKIP Alumni of Tadulako University - Hendra Iskandar; Ardiansyah D Kandupi; Muhammad Ifkhal Sianto (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. The objective of this study is to determine whether Sports Massage can serve as a viable alternative for enhancing the economic well-being of alumni of PJKR FKIP Tadulako University. The research aims to investigate the effectiveness of Sports Massage as a means of generating income for alumni of the aforementioned university. The study will employ a rigorous methodology to collect and analyze data, to provide insights into the potential benefits of Sports Massage for alumni of PJKR FKIP Tadulako University. The findings of this research will be of great significance to policymakers, practitioners, and scholars in the field of sports science and related disciplines. Materials and methods. This study is qualitative descriptive research that employs the interview method. The research population comprises all alumni of the Physical Education and Health Department at Tadulako University who have availed of sports massage services/clinics. The sampling technique employed is purposive sampling, and the sample size consists of five PJKR alumni who meet the criteria. Data analysis techniques include data reduction and conclusion. Results. The findings of this research, based on interviews with a sample of successful Sports Massage clinic owners, demonstrate that Sports Massage can serve as a viable option to enhance the economic well-being of Tadulako University PJKR alumni. Several PJKR alumni from Tadulako University who have pursued a career as sports massage experts have established their businesses and created new job opportunities for other PJKR graduates. In addition to running clinics, they have expanded their services by offering sports and traditional massage services through online platforms such as online ordering (home service). This approach has received positive feedback from the public, as it eliminates the need for customers to visit the clinic and allows them to receive services directly at their homes. Conclusion. Sports Massage has become the primary profession for a group of individuals, who have since expanded to create job opportunities for others. These individuals have reported that opening a Sports Massage clinic or providing home services is a promising business venture, with the average opinion being that the potential income is substantial. As a result, their focus has shifted towards Sports Massage as a lucrative business opportunity.